Karakteristik Sifat Fisik Tanah Gambut Ogan Komering Ilir - Siti Muslikah; Ida Yuliana (Department of Civil Engineering and Planning, Faculty of Engineering, Sriwijaya University, 2021)
Some areas of South Sumatra Province are peatlands scattered in the eastern part, starting from the districts of Musi Rawas, Musi Banyuasin, Ogan Komering Ilir, Muaraenim, and Banyuasin. Around 769,000 hectares of peatland are located in the Ogan Komering Ilir Regency area. Ogan Komering Ilir Regency is an area prone to forest fires. Therefore, it is necessary to conduct research on the characteristics of peat soils in the Ogan Komering Ilir area so that they can be used as consideration in efforts to prevent peatland fires. Sampling was carried out in Kotarayo Village, (Kayuagung District), SP 1 (Pedamaran Timur District), and Tulung Selapan Ilir Village (Tulung Selapan District). Peat soil samples were taken with ASTM D 7015-04 guidelines, and the physical properties of peat soil were tested for samples from the three locations. Based on its physical properties, peat soil samples are classified according to ASTM D4427-84. From the results of the research on peat soils in Kayuagung, Tulung Selapan, and Pedamaran Timur sub-districts, Ogan Komering Ilir Regency, peat soil samples can be classified as sapric-peat soil.